Fluoride-catalyzed addition of PhSCF2SiMe3 to N-substituted cyclic imides followed by radical cyclization: General synthetic strategy of gem-difluoromethylenated 1-azabicyclic compounds - Teerawut Bootwicha (2018)
(Chemical Equation Presented) PhSCF2SiMe3 (1) was found, for the first time, to undergo fluoride-catalyzed nucleophilic difluoro(phenylsulfanyl)methylation reaction to cyclic imides 2, affording the corresponding adducts 3 in moderate to good yields. Reductive cleavage of the phenylsulfanyl group of N-alkylated adducts 3 with Bu3SnH/AIBN yielded gem-difluoromethylated products 4. Under the same reduction conditions, N-alkenylated and N-alkynylated adducts 3 afforded the corresponding gem-difluoromethylenated 1-azabicyclic compounds 5 and 6 with trans stereoselectivity. These compounds were employed as precursors for preparing substituted gem-difluoromethylenated pyrrolizidinones and indolizidinones 7 and 8 by treatment with Et3SiH/BF3·OEt2, and compounds 9 and 10 by nucleophilic displacement of the hydroxyl group, using organosilanes in the presence of BF3·OEt2. The synthesis of highly substituted gem-difluoromethylenated pyrrolizidines 13 and 14 was also demonstrated. © 2009 American Chemical Society.